Implementasi Balanced Scorecard sebagai Pengukuran Kinerja Rumah Sakit Ibnu Sina Pekanbaru - Wahyuni, Putri; Martias, Dony (Basecamp Economics PubMed, 2024)
This research is a quantitative study that aims to determine how the implementation of Ibn Sina Hospital performance measurement with the balance scorecard approach. This study uses primary and secondary data obtained through the company's financial statements and questionnaires filled out by employees and patients. Performance from a customer perspective measured by customer satisfaction indicators measured in the current year shows the level of customer satisfaction in the